USING WEBQUAL 4.0 METHOD TO ANALYZE STUDENT SATISFACTION ON DIGITAL ENTREPRENEUR WEBSITES - Erdisna Erdisna; Sri Restu Ningsih; Weni Kurnia Sari; Tri Monarita Johan (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The Digital Entrepreneur website is an application designed for students so that they can learn to become digital entrepreneurs by utilizing the applications they have created. The problem that occurs is that there are still students who are dissatisfied with using the Digital Entrepreneurship Website application. The aim of the research is to analyze and measure the quality of Digital Entrepreneurship Websites in the student learning process. The method used to measure website quality is WebQual 4.0. Quality assessment uses a questionnaire designed for instruments with dimensions of usability, information quality and interaction quality. The applications used to test the relationship between variables from WebQual 4.0 and user satisfaction are SPSS and Matlab. Research findings reveal that quality is the lowest valued dimension, however, the score for the WebQual 4.0 indicator reaches 70%, categorizing it as Good, leading users to use this website as a valuable educational resource in higher education.